MODELING OF SHORT WAVE PROPAGATION USING FINITE DIFFERENT METHOD - RACHMAN GANDANEGARA (NIM 25505003), EDDY
Short wave formed by wind at deep water propagates shoreward. In this shoreward propagation process, wave is having some transformation process due to variation of water depth or the part of wave hits some obstacles. This wave transformation is shoaling, refraction, diffraction, reflection, and also breaking wave. This transformation process changes the height of propagation wave at every point in transition and in shallow water. Calculation of wave height is very important in sea project such as beach protection project or port design project. But mathematical solution exists for this matter is only for simple problem such as at the case of straight and parallel contour. One way for calculating wave height at transition and shallow water for arbitrary water depth condition is by using numerical model. This thesis is a model development to calculate short wave propagation by using finite different method, where government equation, discretization, boundary condition arrangement for some condition such as forcing boundary, open boundary, and reflective boundary are described. Numerical scheme used in this model development is staggered grid scheme. This scheme is apply in x-direction, y-direction and also in time discretization. Model is solved explicitly. The result from this model is then compared by other solution like analytical solution. In this thesis also, model sensitivity analysis is performed which the result could give guidance how to determine good value of As in using this model.